PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN PROMOSI JABATAN TERHADAP KINERJA KARYAWAN PADA PT. PRIORITAS CABANG BENGKULU - Taufik Bustami; Jiki Heryanto (UM. Bengkulu, 2022)
The role of human resources becomes increasingly important when associated with global developments full of competition among organizations. One of the ways that organizations do in facing competition is by empowering and exploring all the potential of its human resources to the fullest. This study aims to determine the effect of Organizational Citizenship Behavior and promotion on employee performance at PT. Priority Bengkulu Branch. The type of research used in this research is quantitative research with a descriptive approach. The sample in this study 46 employees at PT. Priority Bengkulu Branch. Data collection by using a questionnaire. The analysis technique used is multiple linear regression analysis, coefficient of determination and hypothesis testing. The results showed a positive regression direction with the equation Y = 5.820 + 0.546 (X_1) + 0.324 (X2), meaning that if Organizational Citizenship Behavior and promotions increase, the performance of employees at PT. The priority of the Bengkulu Branch will also increase. The coefficient of determination is 0.717 (meaning that the variable Organizational citizenship behavior (X_1) and job promotion (X2) on the Performance variable contributes 0.717 or 71.7% while the remaining 28.3% is influenced by other variables that are not included in this research model. The results of hypothesis testing for the t-test can be seen that X1 (Organizational citizenship behavior) shows a significance value of 0.000 <0.05, meaning that there is a significant influence of Organizational citizenship behavior on employee performance at PT Prioritas Bengkulu Branch X2 (position promotion) shows a significance value of 0.025 < 0.05, meaning that there is a significant influence of job promotion on employee performance at Prioritas Bengkulu Branch Employees. Simultaneous hypothesis testing shows Organizational citizenship behavior (X_1) and job promotion (X2) together positive effect on the performance (Y) of employees to employees of PT. Priority for Bengkulu Branch because the significant value is 0.000 < 0.05. Keywords: Service Quality, Price, Product Quality, Consumer Satisfaction